On the possession to acquire the domain of a property by acquisitive prescription in Catalonia, Catalonia Superior Court of Justice, December 19th, 2019, resource number 147/2019, resolution number 84/2019 (Justicia &Derecho, 2023)
Regarding the ruling under study, this article seeks to analyze the requirements that possession must meet so that ownership of a property can be acquired by purchasing prescription in accordance with Catalan civil regulations. Along with this, a brief criticism is made of the figure of the acquisitive prescription in Catalonia, comparing its regulation with that of Spanish, Colombian and U.S. law. Finally, a comment is presented on the judgment issued by Catalonia Superior Court of Justice regarding the assessment of evidence and the dation in payment.
Keywords: purchasing prescription